Effects of an eight-week neuromuscular training program on balance and reaction speed in collegiate hadang athletes: A controlled trial - Zubaida, Ida; Yuniarti, Tricahyani Endah; Aqobah, Qory Jumrotul; Ramadhan, Abdul Al Aziz; Saniyyah, Sabrina Zahra Almaas (UIR Press, 2025)
Background: Hadang is a traditional Indonesian team sport that demands a high level of whole-body reaction time and unilateral postural control. Various training modalities have been shown to improve key physical components which collectively support performance in fast-paced games like the hadang. However, evidence on the effectiveness of neuromuscular training in this sport is limited. Objectives: This study aimed to evaluate the impact of 8 weeks of neuromuscular training on balance and reaction speed in university-level Hadang athletes. Methods: A quasi-experimental, controlled pretest–posttest design with two parallel groups was used. Thirty athletes were allocated to either a neuromuscular training group (NTG; n = 15; 3 sessions/week for 8 weeks; 30–40 minutes/session) or a control training group (CTG; regular training without neuromuscular training). Primary outcomes were unilateral balance and whole-body reaction time. Data were analyzed using 2 × 2 mixed-design ANOVA, with paired t-tests for simple effects. Findings/Results: Compared to CTG, NTG demonstrated significant improvements in balance and significant decreases in whole-body reaction time, while changes in CTG were not substantial. Conclusion: Eight weeks of structured neuromuscular training effectively improved balance and reaction time in college-level hadang athletes, with moderate effect sizes for balance and large effects for reaction time. Given its simplicity, minimal equipment requirements, and compatibility with standard training microcycles, neuromuscular training is worthy of adoption as a core, evidence-based component of performance periodization for hadang.